2016
DOI: 10.1002/2016gl071646
|View full text |Cite
|
Sign up to set email alerts
|

Ring current pressure estimation with RAM‐SCB using data assimilation and Van Allen Probe flux data

Abstract: Capturing and subsequently modeling the influence of tail plasma injections on the inner magnetosphere is important for understanding the formation and evolution of the ring current. In this study, the ring current distribution is estimated with the Ring Current‐Atmosphere Interactions Model with Self‐Consistent Magnetic field (RAM‐SCB) using, for the first time, data assimilation techniques and particle flux data from the Van Allen Probes. The state of the ring current within the RAM‐SCB model is corrected vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Challenges further lie in how to take full advantage of the rapidly growing massive satellite measurements and maturing physics-based models by using effective tools, such as machine learning and data assimilation. While these techniques have been widely and successfully applied in the ionosphere, they are quite limited in the inner magnetosphere field (there are only a few research groups dedicating to this area, e.g., Chu et al, 2017;Godinez et al, 2016;Kellerman et al, 2014;Shprits et al, 2013;Zhelavskaya et al, 2017). How to extend their application to other geospace regions and dynamics to achieve a full 3-D representation of the inner magnetosphere is one challenging objective.…”
Section: Future Challengesmentioning
confidence: 99%
“…Challenges further lie in how to take full advantage of the rapidly growing massive satellite measurements and maturing physics-based models by using effective tools, such as machine learning and data assimilation. While these techniques have been widely and successfully applied in the ionosphere, they are quite limited in the inner magnetosphere field (there are only a few research groups dedicating to this area, e.g., Chu et al, 2017;Godinez et al, 2016;Kellerman et al, 2014;Shprits et al, 2013;Zhelavskaya et al, 2017). How to extend their application to other geospace regions and dynamics to achieve a full 3-D representation of the inner magnetosphere is one challenging objective.…”
Section: Future Challengesmentioning
confidence: 99%
“…For example, in data assimilation for the interior of the Earth, such as lithospheric plates (e.g., Kano et al, 2015) and the outer core (e.g., Sanchez et al, 2019;Minami et al, 2020), the timescale of the system dynamics is so long that a sufficient length of an observation sequence is not feasible. It is also difficult to use a long sequence of observations in the Earth's magnetosphere where the amount of observations is limited (e.g., Nakano et al, 2008;Godinez et al, 2016). It is therefore an important issue to consider large uncertainties which could deteriorate the validity of the linear approximation.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have suggested that estimations in nonlinear problems can be improved by iterative algorithms in which the ensemble is repeatedly updated in each iteration (e.g., Gu and Oliver, 2007;Kalnay and Yang, 2010;Chen and Oliver, 2012;Sakov, 2013, 2014;Raanes et al, 2019). These iterative algorithms can be regarded as a S. Nakano: Ensemble variational method variant of the 4DEnVar method, based on an approximation of the Gauss-Newton method or the Levenberg-Marquardt method.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in data assimilation for the interior of the Earth such as lithospheric plates (e.g., Kano et al, 2015) and the 20 outer core (e.g., Sanchez et al, 2019;Minami et al, 2020), time scale of system dynamics is so long that a sufficient length of an observation sequence is not feasible. It is also difficult to use a long sequence of observations in the Earth's magnetosphere where the amount of observations is limited (e.g., Nakano et al, 2008;Godinez et al, 2016). It is therefore an important issue to consider large uncertainties which could deteriorate the validity of the linear approximation.…”
Section: Introductionmentioning
confidence: 99%